A novel strategy to construct the superior performance of 3D multi-shell CeO2/ZnO@ZnS as a reusable sunlight-driven ternary photocatalyst for highly efficient water remediation. Issue 4 (August 2021) - Jiang, Xiaoqing; Huang, Linsen; Li, Junhua; Zhang, Liangxing; Guo, Xinyu; Li, Yiqing; Sun, Xiaosong
Abstract: In this work, a novel three-dimensional (3D) multi-shell CeO2 /ZnO@ZnS (CZS-X) photocatalyst has been successfully designed and fabricated. The morphology, chemical and optical properties have been characterized in detail and verified its photocatalytic efficiency via the degradation of p-Nitrophenol. It is found that such ternary CZS-1.5 with oxygen vacancies gives rise to a significantly enhanced photocatalytic performance under simulated sunlight (97%, 25 min). Thus, a dual type-II heterojunction mode of charge migration mechanism is proposed, which rationally describes the separation and transmission efficiency of carriers. Moreover, the carrier mobility is also affected by ZnS nanoshell, which not only upgrades the photodegradation activity of ZnO nanorods, but also suppresses the photocorrosion of ZnO during the catalytic reaction, resulting in the acquired reusability of CZS-1.5. This study introduces the new inspiration for catalyst modification, conquering the inherent properties of materials and providing a new perspective for environmental restoration and solar energy utilization. Graphical Abstract: ga1 Highlights: Feasible design and interface improve the catalytic behavior of nanocomposites. Morphologies of photocatalyst were controlled by different experimental condition. The CeO2 /ZnO@ZnS photocatalyst exhibits outstanding photocatalytic performance and recyclability. Dual type-II heterojunction and oxygen vacancies can promote carriers' transfer and separation.